2018
DOI: 10.1103/physrevx.8.031002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Tests of the Chiral Anomaly Magnetoresistance in the Dirac-Weyl Semimetals Na3Bi and GdPtBi

Abstract: In the Dirac/Weyl semimetal, the chiral anomaly appears as an "axial" current arising from charge-pumping between the lowest (chiral) Landau levels of the Weyl nodes, when an electric field is applied parallel to a magnetic field B. Evidence for the chiral anomaly was obtained from the longitudinal magnetoresistance (LMR) in Na3Bi and GdPtBi. However, current jetting effects (focussing of the current density J) have raised general concerns about LMR experiments. Here we implement a litmus test that allows the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(175 citation statements)
references
References 23 publications
(33 reference statements)
8
161
4
2
Order By: Relevance
“…A final word about the evaluation of the topological character of ZrSiSe. We indeed observed negative longitudinal magnetoresistivity, claimed in Dirac and Weyl systems to result from the chiral anomaly among Weyl points (35). But after a detailed analysis on the current distribution (35), we concluded that it results from the so-called current jetting effect (35), i.e.…”
Section: Discussionmentioning
confidence: 67%
“…A final word about the evaluation of the topological character of ZrSiSe. We indeed observed negative longitudinal magnetoresistivity, claimed in Dirac and Weyl systems to result from the chiral anomaly among Weyl points (35). But after a detailed analysis on the current distribution (35), we concluded that it results from the so-called current jetting effect (35), i.e.…”
Section: Discussionmentioning
confidence: 67%
“…Fermi-arcs in the surface states have been conclusively measured by several groups using angleresolved photoemission spectroscopy [6][7][8][9][10][11], and further confirmed by local spectroscopic techniques [13][14][15][16]. Moreover, as Weyl Fermions coupled to electromagnetic fields lead to non-conservation of chiral charges -the so called Adler-Jackiw anomaly [17] -its signatures were investigated in magnetotransport experiments, with some concern regarding the possible role of inhomogeneous current flow in bulk crystals [18][19][20]. Although major efforts have been put in the fabrication of WSMs micro-structures from bulk crystals by focused ion beam milling [21][22][23][24], thereby enabling advanced thermal transport experiments [21], fabrication-related property changes of the WSMs had to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…This also gives rise to a chiralanomaly-induced negative MR depending on the H-field direction. Figure 5a shows the longitudinal magnetoconductivity (MC, the inverse of MR) as a function of the magnetic field H for the [001] direction at several temperatures below 6 K. The peak in the low magnetic field region is due to the weak antilocalization effect, which has been observed in other Dirac and Weyl semimetals [41,42]. For the high magnetic field region (H ≥ 2 T), a positive MC (negative MR) is observed.…”
Section: Resultsmentioning
confidence: 86%